Beyond the surface: analyzing etomidate and propofol as anesthetic agents in electroconvulsive therapy—A systematic review and meta-analysis of seizure duration outcomes - Akhtar, Syed M. M.; Saleem, Syed Z.; Rizvi, Syed H. A.; Raja, Sandesh; Asghar, Muhammad Sohaib (Frontiers in Neurology, 2023)
Background Electroconvulsive therapy (ECT) is a widely used treatment for severe psychiatric disorders such as schizophrenia, depression, and mania. The procedure involves applying brief electrical stimulation to induce a seizure, and anesthesia is used to ensure sedation and muscle relaxation. Finding the right anesthetic agent with minimal side effects, especially on seizure duration, is crucial for optimal outcomes because seizure duration is an important factor in the effectiveness of ECT, but the anesthetic agents used can affect it. Objective This systematic review and meta-analysis aimed to pool the results of all relevant studies comparing the two induction agents, etomidate and propofol, for motor and electroencephalogram (EEG) seizure duration outcomes. Methods A comprehensive literature search was conducted in the PubMed, Medline, and Cochrane Library databases to identify the relevant articles. The primary outcome measures were motor and EEG seizure durations. Statistical power was ensured by performing heterogeneity, publication bias, sensitivity analysis, and subgroup analysis. Standard mean difference and 95% confidence intervals were calculated for continuous outcomes, and a random-effects model was used. Results A total of 16 studies were included in this meta-analysis, comprising 7 randomized control trials (RCTs), 7 crossover trials, and 2 cohorts. The overall motor seizure duration was statistically significantly longer with etomidate than with propofol. The overall result for EEG seizure duration was also longer with the use of etomidate over propofol and was statistically significant. In addition, subgrouping was performed based on the study design for both outcomes, which showed insignificant results in the cohort's subgroup for both outcomes, while the RCTs and crossover subgroups supported the overall results. Heterogeneity was assessed through subgrouping and sensitivity analysis. Conclusion Our meta-analysis found that etomidate is superior to propofol in terms of motor and EEG seizure duration in ECT, implying potentially better efficacy. Hence, etomidate should be considered the preferred induction agent in ECT, but larger studies are needed to further validate our findings.